Analisis Pengaruh Kenyamanan dan Kualitas Produk Terhadap Kepuasan Konsumen pada Motor Listrik PT. Len Industi (Persero) di Lingkungan Militer TNI. - Tri Rezki Putri Larasati; Nuniek Dewi Pramanik (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research aims to analyze the perception of comfort in driving electric motorcycles among TNI military personnel at PT. Len Industri (Persero) to identify factors influencing comfort and measure the impact of PT. Len Industri (Persero) electric motorcycle product quality on interest and satisfaction in the military environment. The study adopts a quantitative method, employing purposive sampling with a total sample of 40 respondents. Data collection involves distributing Likert scale questionnaires to consumers or TNI military personnel using PT Len Industri (Persero) electric motorcycles. The author employs data analysis techniques such as validity testing, reliability testing, normality testing, t-test, F- test, and R-test. The data obtained are processed using SPSS 29. Based on the results of the t-test, the calculated r-value is 5.323 > r-table 1.686, and a significant value of 0.00 < 0.05 is obtained, indicating that the related variables are influenced by independent variables. Referring to the coefficient of determination test results, an R square value of 86.7% is obtained. Thus, based on the analysis conducted, it is concluded that customer satisfaction is influenced by rider comfort and product quality.